The Coins of Philip the Tetrarch and the Imperial Cult: A View from Paneas on the Fall of Sejanus - Giambrone, Anthony (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2021)
Abstract Philip the Tetrarch, son of Herod the Great, was the first Jewish ruler to depict human images on his coins. This innovation of adopting numismatic portraiture must be understood in inseparable conjunction with Philip’s aggressive cultivation of the imperial cult at Paneas. The present article, accordingly, offers the first focused study of how the development of iconography on his issues corresponds to specific political events of cultic concern. In this connection, a new interpretation is suggested for Philip’s unique undated minting, deeply implicated in the imperial drama transpiring around the year 31 CE . The tetrarch’s savvy manipulation of images, when seen against this broad background, reveals his unwavering and intensifying allegiance to the domus Augusta : to the princeps in the form of a clipeus virtutis devotion and to Livia under the aspect of Demeter.